2013
DOI: 10.5009/gnl.2013.7.1.96
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics of Patients with Autoimmune Pancreatitis with or without Mikulicz's Disease and Mikulicz's Disease Alone

Abstract: Background/AimsThe objective of this study was to compare the clinical characteristics of patients with autoimmune pancreatitis (AIP) with or without Mikulicz's disease (MD) and with MD alone.MethodsWe investigated the clinical findings in 15 AIP patients with MD (group A+M), 49 AIP only patients (group A), and 14 MD only patients (group M).ResultsThe male-female ratio was significantly higher in group A+M (73%, p<0.05) and group A (78%, p<0.01) than group M (21%). Serum immunoglobulin G (IgG) levels were sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…IgG4‐RD is widely acknowledged to affect men more commonly than women, as observed in our cohort . The disparity between sexes in this cohort, however, was less prominent than has often been reported in the literature (male:female ratio 1.6:1).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…IgG4‐RD is widely acknowledged to affect men more commonly than women, as observed in our cohort . The disparity between sexes in this cohort, however, was less prominent than has often been reported in the literature (male:female ratio 1.6:1).…”
Section: Discussionsupporting
confidence: 46%
“…Most of the literature on IgG4‐RD consists of case reports and small case series focused on individual organ manifestations, particularly the pancreas, kidney, biliary tree, and salivary glands . In the present study, we provide a detailed analysis of the clinical features of the first 125 patients diagnosed as having IgG4‐RD at the Massachusetts General Hospital with diagnostic confirmation based on strict correlation with the clinicopathologic findings.…”
mentioning
confidence: 96%
“…In fact, the 5 cases in our hospital with serum IgG4 that was not elevated did not relapse. Among patient background factors, IgG4-related sclerosing cholangitis, obstructive jaundice, immune complex value, diffuse pancreatic ductal changes, and sclerosing sialadenitis have been proposed as relapse factors [ 6 , 15 18 ]. Studies of the serum IgG4 level have proposed the following predictive factors for relapse: high serum IgG4 at initial diagnosis [ 11 , 19 21 ], a high level before and after treatment [ 4 ], and resurgence of serum IgG4 in the remission phase after treatment [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Kamisawa et al, 2013 Our analysis revealed the prevalence of AIP in patients with IgG4‐RS as 20.47% (CI [16.20%, 25.06%]), and complication by AIP tended to be correlated with the recurrence of IgG4‐RS, Yamamoto, Nojima, et al, 2015 and the presence of IgG4‐RS was also determined to be an independent risk factor for relapse in patients with AIP. Ishii et al, 2019 Kuruma et alKuruma et al, 2013 reported that the relapse rate of AIP in patients with IgG4‐RS was significantly higher than in patients without IgG4‐RS. As the pancreas is the most frequently affected organ in IgG4‐RD, routine follow‐up is required, even if no pancreatic involvement is found at initial diagnosis.…”
Section: Discussionmentioning
confidence: 99%